Self-Reported Health and Functional Characteristics of Mexican and Mexican American Adults Aged 80 and Over - Downer, Brian (J Aging Health, 2016)
OBJECTIVE: To examine the health and functional characteristics of Mexican and Mexican American adults aged ≥80. METHOD: Data came from Wave I (2001) and Wave III (2012) of the Mexican Health and Aging Study (MHAS), and Wave IV (2000–2001) and Wave VII (2010–2011) of the Hispanic Established Populations for Epidemiologic Studies of the Elderly (HEPESE). RESULTS: In 2000–2001, diabetes, arthritis, hypertension, and stroke were higher in the HEPESE than in the MHAS. In the HEPESE, activities of daily living (ADL) difficulties and all health conditions, except heart attack, were greater in 2010–2011 than in 2000–2001. In the MHAS, hypertension and ADL difficulties were greater, and arthritis was lower in 2012 compared with 2001. In 2010–2011, all self-reported health conditions were higher in the HEPESE compared with the 2012 observation of the MHAS. DISCUSSION: The observed differences may reflect worse health for Mexican Americans, health care access, reporting bias, and more selective survival to very old age in Mexico.